Communication in the Implementation of Cellular Phone Prepaid Card Registration Policies Using Family Identification Numbers and Family Cards: Komunikasi Dalam Implementasi Kebijakan Registrasi Kartu Prabayar Telepon Seluler Menggunakan Nomer Induk Keluarga dan Kartu Keluarga - Pramesti, Ayu Keke; Riyadh, Ahmad (Universitas Muhammadiyah Sidoarjo, 2020)
Data analysis used the Miles and Huberman interactive model analysis which consisted of data collection, data reduction and data presentation. The results of the study show that the implementation of the policy of registering prepaid cell phone cards using NIK and KK Numbers at the Sidoarjo Communication and Information Office can be seen from: a) Communication, indicating that the delivery of prepaid cell phone card registration using NIK and KK to the target group which in this case is community is done through socialization. Initial socialization was carried out in 2017; b) Resources, indicating that the existing employees are considered sufficient when viewed in terms of quality and quantity. In terms of facilities, the existing facilities are in good condition and are still suitable for use in the registration of prepaid cell phone cards using NIK and KK; c) Disposition, indicating that the attitude and commitment of the cellular phone prepaid card registrar using the NIK and KK in carrying out their duties is in accordance with the code of ethics. If there is a discrepancy in the implementation of prepaid cell phone registration using NIK and KK, the executor will give awards in the form of money and certificates as well as punishment or consequences that depend on the superiors; d) Bureaucratic structure, indicating that there has been a match between the implementing structure in the implementation of prepaid cellular phone card registration using NIK and KK.